The relation between resting alpha power and behavioural activation system sensitivity - Sorjonen, Emmi (2020)
The behavioural activation system (BAS) and the behavioural inhibition system (BIS) have been found as neural systems that seem to regulate approach or withdrawal behaviours. Since the alpha asymmetry has in earlier EEG (electroencephalographic) -studies been found to correspond to neuronal activation and being related to motivational direction systems, we were interested to measure the alpha activation with more accurate MEG (magnetoencephalography) –method. The aims of present report were to clarify if behavioral activation system (BAS) relates to resting alpha, to see if there is alpha asymmetry and if the alpha asymmetry is related to differences in behavioural tendencies. Data was collected using MEG and a questionnaire from a sample of 46 participants. The resting state was measured during 12 minutes with MEG and tendency for behavioral inhibition vs. activation was evaluated by BIS/BAS questionnaire. Main result of the present study is that the value of behavioral activation system BAS (BAS Drive) was correlated with level of alpha oscillation in frontal areas. The finding indicates that frontal alpha activation increases when the BAS score decreases. This means that those who have stronger resting alpha activity are less motivated by following one’s goals. More MEG studies are needed to clarify this relation between resting alpha and behavioral tendencies.